Electrical and Mechanical Properties of Plated Ni/Cu Contacts for Si Solar Cells. (August 2015) - Kluska, Sven; Bartsch, Jonas; Büchler, Andreas; Cimiotti, Gisela; Brand, Andreas A.; Hopman, Sybille; Glatthaar, Markus
Abstract: Plated Ni/Cu/Ag contacts are an industrially feasible metallization approach for high efficiency c-Si solar cells with low surface doping concentrations (10 18 cm -3 < N D < 10 20 cm -3 ). The 2d-simulations of this work define the minimum requirements on the contact resistivity of metal contacts in a high efficiency solar cell design. The following experimental study of the contact resistivity of plated Ni/Cu/Ag contacts on lowly doped phosphorus emitter demonstrates low contact resistivities in the mΩcm 2 regime, which enable solar cells with high fill factors. Furthermore, the paper analyzes the influence of the thermal silicidation process on pseudo-fill factor losses and on the mechanical contact adhesion. The contact adhesion is also studied with respect to the laser contact opening process. The results of this work demonstrate that the right choice of back-end processes enable plated Ni/Cu/Ag contacts with low contact resistivities in combination with high contact adhesions above 1 N/mm.